The Effectivity of Himmati to Improve the Arabic Reading Skills Through the Online ATQ Program - Himatul Istiqomah; Nurul Murtadho; Hanik Mahliatussikah; Yhusi Karina Riskawati; Mohammad Jawad Habeeb Al-Badrani (Universitas Negeri Malang, 2021)
This article aimed to verify the effectivity of Himmati to improve the Arabic reading skills of beginners. The target population here was all of the beginners in Indonesia as well as some other countries in Southeast Asia. While the accessible population was the beginners in MAN 4 Banyuwangi, Indonesia among the new students of 2020/2021. Based on the experiment results on 21 samples who participated in the online ATQ program using Himmati, which were analyzed with the paired-sample t-test, it was found a value of sig. (2-tailed) 0,000 < P-value 0,50, while the value of tcount 5,901 > ttable 2,086. It showed that there was difference in the Arabic reading skills for beginners between pretest and post-test scores. Because the post-test score 87,19 > pretest score 80,38. So it can be concluded that Himmati is effective as a textbook to improve the Arabic reading skills for beginners in MAN 4 Banyuwangi. Thus, Himmati can be recommended as a textbook to be used by more beginners to improve the Arabic reading skills.